The Case of the Suzhou Hospital of National Medicine (1939–41): War, Medicine, and Eastern Civilization. Issue 2 (1st June 2017) - Daidoji, Keiko; Karchmer, Eric I.
Abstract : This article explores the founding of the Suzhou Hospital of National Medicine in 1939 during the Japanese occupation of Suzhou. We argue that the hospital was the culmination of a period of rich intellectual exchange between traditional Chinese and Japanese physicians in the early twentieth century and provides important insights into the modern development of medicine in both countries. The founding of this hospital was followed closely by leading Japanese Kampo physicians. As the Japanese empire expanded into East Asia, they hoped that they could revitalize their profession at home by disseminating their unique interpretations of the famous Treatise on Cold Damage 傷寒論 abroad. The Chinese doctors that founded the Suzhou Hospital of National Medicine were close readers of Japanese scholarship on the Treatise and were inspired to experiment with a Japanese approach to diagnosis, based on new interpretations of the concept of "presentation" ( shō / zheng 證). Unfortunately, the Sino-Japanese War cut short this fascinating dialogue on reforming medicine and set the traditional medicine professions in both countries on new nationalist trajectories.